The Influence of Product Types and Promotion on Customer Loyalty at Ifarma Pharmacy Kebo Iwa Denpasar - Listiani, Putu Ayu Ratih; Oviani, Gusti Ayu; Dewi, Putu Putri Purnama (Poltekkes Kemenkes Denpasar, 2025)
The increasingly fierce business competition in the pharmaceutical industry requires pharmacies to continuously improve their strategies to retain and attract customers. This study aims to analyze the influence of product types and promotion on customer loyalty at IFarma Pharmacy Kebo Iwa Denpasar. The research method used is quantitative, employing a survey approach with questionnaires distributed to pharmacy customers. The population in this study consisted of IFarma Pharmacy customers who made purchases at IFarma Pharmacy Kebo Iwa during March 2025. Samples were taken using a purposive sampling technique, totaling 222 respondents. The characteristics of the respondents obtained were 55.9% (124 people) female, the majority of respondents were between 20 and 40 years old, totaling 185 people (83.3%), the highest level of education was high school 49.5% (110 people), 196 respondents were employed (88.29%), with the majority earning between IDR 2,000,000 - 5,000,000, totaling 105 people (47.30%), and a frequency of 2-3 visits was reported by 121 people (54.50%). The results showed that the regression coefficient for the promotion variable was 0.224, meaning that a 1% increase in promotion would increase customer loyalty to IFarma Pharmacy Kebo Iwa by 22.4%. The positive value of 0.224 indicates a positive correlation between the variety of products offered and effective promotional strategies, which positively and significantly influence customer loyalty. This confirms the importance of providing diverse products and targeted promotions to enhance customer satisfaction and commitment to repeat purchases. This research is expected to serve as a reference for pharmacy managers in formulating more effective marketing strategies to maintain customer loyalty amid increasingly competitive market conditions.